Assessment of Fruit Rot Disease Incidence in Chili Caused by Alternaria spp. in Telangana State - Terrance, Irene; Sagar, B. Vidya; Padmaja, G.; Rajanikanth, P. (International Journal of Economic Plants, 2025)
A roving survey was conducted during rabi (December, 2023) in major chilli producing areas of Telangana i.e., Warangal, Mahabubabad and Khammam to assess the fruit rot incidence and distribution in the state. Samples were collected at harvesting stage from 14 villages of 3 districts in Telangana. Maximum disease incidence of 67.59% was observed in Jagguthanda village of Khammam district and minimum disease incidence of 9.90% was recorded in Banjarathanda village of Mahabubabad district. Maximum mean disease incidence was observed in Khammam district (36.45%) followed by Warangal (36.29%). Chapata variety exhibited maximum mean incidence (55.60%) and Teja gemini exhibited minimum mean incidence (21.78%). Fruit rot incidence was more in red chalka soil (48.93%) followed by sandy loam soil (40.13%). Maximum mean disease incidence was observed in flooding (42.45%) and minimum mean disease incidence was noticed in check furrow (17.31%). Farmers cultivating chilli over years without crop rotation is also a reason for severe incidence of chilli fruit rot. In the field symptoms of leaf curl and traces of fusarium wilt was observed. According to Principal Component Analysis (PCA), it was found two principal components are significant, and percentPercent disease incidence has a strong influence on the principal components. % disease incidence contributed maximum to variance followed by village, soil type, variety and irrigation. In PCA biplot, variables in the same direction and close to each other have a positive correlation. Results showed positive correlation for variety and irrigation.